Managing Teacher Competence in Android-Based Differentiated Instruction: A Qualitative Study in Indonesian Vocational Education - Hasriyani Hasriyani; Nurdin K; Muhammad Guntur (Har Press Indonesia, 2024)
This study examines the management of teacher competence in implementing Android-based differentiated instruction within a vocational education context. Grounded in the increasing demand for technology-integrated and student-centered learning, this research aims to analyze (1) the managerial processes underlying teacher competence development, (2) the characteristics of Android-based differentiated instruction, and (3) the multidimensional competencies required by teachers. A qualitative descriptive design was employed, with data collected through in-depth interviews, participant observation, and document analysis involving school leaders, teachers, and students at SMK Negeri 2 Palopo, Indonesia. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that teacher competence management operates through a systematic cycle of planning, organizing, implementation, and evaluation, supported by institutional structures and continuous professional development. Android-based differentiated instruction is characterized by personalization, interactivity, flexibility, real-time monitoring, and collaborative learning environments. Furthermore, teacher competence is identified as a multidimensional construct encompassing technological, pedagogical, evaluative, managerial, and motivational dimensions. This study contributes to the discourse on digital pedagogy by highlighting that effective technology integration is contingent upon strategic competence management within educational institutions. The findings offer practical implications for policy and practice in enhancing teacher capacity and advancing adaptive, inclusive, and technology-driven learning systems.